Clinicopathological characteristics, treatment patterns and outcomes in patients with HER2-positive breast cancer based on hormone receptor status: a retrospective study - Ran Ran; Shidi Zhao; Yan Zhou; Xinyue Hang; Hui Wang; Yuan Fan; Yusi Zhang; Yifan Qiao; Jin Yang; Danfeng Dong (BMC Cancer, 2024)
Abstract Background Different hormone receptor (HR) expression patterns have significant biological and therapeutic implications in patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer. However, the distinction between HR-positive /HER2-positive (HR+/HER2+) and HR-negative/HER2-positive (HR-/HER2+) subtypes remains unclear. Methods This retrospective study analyzed 828 patients with HER2-positive breast cancer at the First Affiliated Hospital of Xi’an Jiaotong University from 2012 to 2022. Baseline characteristics were compared by chi-square test. Survival outcomes were estimated by Kaplan-Meier method. Results In total, 56.3% (n = 466) had HR-positive and 43.7% (n = 362) had HR-negative disease. Comparatively, HR+/HER2 + breast cancers presented favorable clinicopathological features. At a median follow-up of 49 months, 199 disease-free survival (DFS) events and 99 deaths were observed. HR+/HER2 + patients had significantly better survival outcomes than HR-/HER2 + patients. HR-positive status was an independent protective factor for overall survival (OS) [P = 0.032; hazard ratio, 0.61; 95% confidence interval (CI), 0.39–0.96] and DFS (P = 0.001; hazard ratio, 0.61; 95% CI, 0.46–0.81). HR+/HER2 + patients were significantly less sensitive to neoadjuvant therapy than HR-/HER2 + patients. In the first-line treatment for HR+/HER2 + advanced breast cancer, receiving endocrine therapy significantly improved advanced-OS (P < 0.001; hazard ratio, 0.33; 95% CI, 0.18–0.59) and progression-free survival (PFS) (P < 0.001; hazard ratio, 0.38; 95% CI, 0.25–0.58) compared with not receiving endocrine therapy. Moreover, maintenance endocrine therapy after HER2-targeted therapy and chemotherapy is associated with significant advanced-OS and PFS benefits compared with no maintenance endocrine therapy (advanced-OS: P < 0.001; hazard ratio, 0.05; 95% CI, 0.03–0.12; PFS: P < 0.001; hazard ratio, 0.35; 95% CI, 0.21–0.57). Conclusions This study reveals the high heterogeneity of HER2-positive breast cancer related to HR status in clinicopathological features, metastasis patterns, and outcomes. Large randomized controlled trials are warranted to optimize treatment strategies for the HER2-positive breast cancer population.